Prospects for rice yield improvement in the post-green revolution Philippines - Pingali, P. L.; Moya, P. F.; Velasco, L. E. (1990)
Evidence from farm level and experimental data from the Philippines indicates a trend towards stagnation and/or a decline in irrigated rice yields when intensively cultivated, even under scientific management on experiment station. Given current rice technology, there is a minimal yield gap between the experiment station and the "best" irrigated farms in the Philippines. If the current yield frontier does not shift outwards, the long-term prospects are for stagnation and/or decline in farm yield. The current yield gap is no longer between the farmer and the experimental potential but rather between farmers themselves.This gap between farmers' yields can be explained by differential farmer ability and differential access to irrigation water. The results of the study suggests that the first priority for rice research ought to be the breaking of the current irrigated yield ceiling.It also indicated that the yield gap between farmers can be reduced by carefully targeted extension-training program and improvement of the efficiency and reliability of water delivery to farms in the middle and tail sections of the system.
Keywords: Rice yields